Effects of content marketing on attitude formation in the South African energy drink market - Hirschfelder, Benedikt (School of Management Studies, 2016)
The rapid technological innovation of the last decade has altered the way people understand and communicate information. The internet specifically has made possible unprecedented access to information which has added another dimension to consumer and marketing practitioner behaviour. The most salient consequence of these developments in the marketing communication arena has been the transition from domination by the marketing practitioner to that of the consumer. More precisely, the huge product variety and the access to non-commercial information in terms of user-generated content gives the consumer incredible autonomy. Facing these circumstances, marketing practitioners are adjusting their strategies in producing informative or entertaining content to surround their product in order to impact the new complex, user-driven market. This specific type of content driven marketing is referred to as content marketing. While the idea of providing useful content around the product/brand is a well-known marketing strategy, consistent technological innovation enables marketers to approach the consumer in a different way. Encouraged by a proliferation of user-generated content, marketing practitioners have already embraced content marketing and established a considerable case series of effective examples. Nevertheless, a scholarly analysis of the impact of content marketing on attitude formation has not yet occurred. Thus the goal of this thesis is to unpack content marketing, and explore its impact on the consumer in order to locate content marketing within Integrated Marketing Communications. Specifically, this study investigates how consumers perceive the sponsor through content marketing, and if emotions triggered by this content influence consumer attitudes towards the sponsor. In order to substantiate the theoretical discourse with practical evidence, a video from the energy drink manufacturer Red Bull serves as a research object and real-world example. By demonstrating the particular strengths of the medium, this thesis aims to establish an academic foundation for the analysis of content marketing, and contribute to the content marketing renaissance.